Calculation of Risk Weighted Assets (RWA) via Machine Learning Technique - Kumar, Prabhat (Indian Journal of Computer Science, 2017)
RWAs have limited literature and confidence in reported RWAs is ebbing. Market participants question the reliability and comparability of capital ratios, and contend that banks may not be as strong as they are portrayed by risk-based capital ratios. With this paper, an altogether new idea was proposed to calculate RWA across banking industries. Machine learning approach will strengthen its calculation engine and make it more robust over time. It will predict the required RWAs on the basis of historical data and expectation feeds. As we know, machine learning is the vital concept of 21st century and can be harnessed in finance domain for evaluation of various risk attributes dynamically and can be tested in normal as well as stressed conditions.